The implementation of clinical quality control in mammography exams: Challenges for professionals and managers - Piva, Izabel C D; Gonçalves, Geórgia; Melo, Juliana de Almeida Coelho de; Huhn, Andrea (Seven Editora, 2023)
Introduction: Mammography is the gold standard for diagnosis of breast cancer, a good positioning guarantees a more accurate diagnosis, being in most cases a great challenge for the professionals of the radiological techniques. The implementation of a clinical quality control program helps to create strategies to minimize nonconformities caused by positioning errors. Objective: To analyze how the implantation of clinical quality control in mammography occurred and what were the results referring to the positioning in the period from 2014 to 2016. Methodology: This was a mixed approach of an applied nature. The data were collected from February to April 2019, in the database of the radiodiagnosis service and through an interview with the coordinator of the service and the radiologist. Results: Since the implantation of the clinical quality control program were found several challenges among them to change the positioning culture, self- evaluation criteria, the main challenge of professionals and managers is to maintain the quality standard of mammographic images. In the period from 2014 to 2016, 8,500 mammography examinations were evaluated and 13,827 nonconformities were found, distributed between the following incidences: caudal skull and lateral oblique lateral. The most evident nonconformities are related to the absence of the pectoralis major in the caudal cranial incidence with the greatest number of errors, being present in 65.6% of the mammographic images. Then the pectoral muscle at the nipple height with 32.7% and pectoral muscle contracted with 21.7% at the oblique mediolateral incidence. Conclusion: The clinical quality control program is an excellent strategy to identify routine errors for a more accurate diagnosis. With continuous training of radiology professionals, the program can be even more effective. DOI:https://doi.org/10.56238/devopinterscie-279